Optimal International Reserves in Lesotho - Molapo, Senei Solomon (European Scientific Journal, ESJ, 2016)
Literature has addressed the issue of choosing reserves levels in the context of models based on traditional adequacy ratio. Above that, this study employs the model of Jeanne and Rancière (2006), which captured the unique characteristics of a country, and effects of a small and large external shocks portrayed that international reserves in Lesotho are kept at level higher than the optimum level. The results outlined that optimum level of reserves for Lesotho is on average 44 per cent of GDP for a small crisis and 47 per cent of GDP for a larger crisis. Subsequently, this leads to the conclusion that the amount of reserves exceeding the level of backing assets could be managed under a more return-oriented investment strategy in order to minimize the opportunity cost of reserves holding. Since there is evidence of excess funds, the authorities should strengthen the implementation capacity of the annual capital budgets by evolving a forceful and vigorous monitoring and evaluation framework in order to accomplish the National Vision 2020 goals. This will also create an opportunity to allocate resources to the National Strategic Development Plan (NSDP) which provides overall national strategic thrust from 2012 to 2016.